2016
DOI: 10.3390/ijms17091529
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Small RNAs in Streptococcus mutans under Acid Stress—A New Insight for Caries Research

Abstract: Streptococcus mutans (S. mutans) is the major clinical pathogen responsible for dental caries. Its acid tolerance has been identified as a significant virulence factor for its survival and cariogenicity in acidic conditions. Small RNAs (sRNAs) are recognized as key regulators of virulence and stress adaptation. Here, we constructed three libraries of sRNAs with small size exposed to acidic conditions for the first time, followed by verification using qRT-PCR. The levels of two sRNAs and target genes predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…[ 14 ]. Additionally, specific sRNAs of a small size (18–50 nucleotides) are specifically induced under acid stress conditions, as revealed in our previous studies [ 15 ]. However, all previous studies were performed with planktonic cells, and very little is known regarding the sRNAs obtained from attached cells, which exhibit different physiological properties from their planktonic counterparts [ 16, 17 ].…”
Section: Introductionmentioning
confidence: 53%
“…[ 14 ]. Additionally, specific sRNAs of a small size (18–50 nucleotides) are specifically induced under acid stress conditions, as revealed in our previous studies [ 15 ]. However, all previous studies were performed with planktonic cells, and very little is known regarding the sRNAs obtained from attached cells, which exhibit different physiological properties from their planktonic counterparts [ 16, 17 ].…”
Section: Introductionmentioning
confidence: 53%
“…Importantly, sRNAs coordinate adaptation processes in response to environmental changes in bacteria by regulating target mRNA expression [37][38][39][40][41]. Specifically, srn225147 and srn821798 were sequenced in our previous studies [22,23]. Virulence-related genes selected in our present study were predicted targets for these two sRNAs according to IntaRNA and RNAPredator.…”
Section: Discussionmentioning
confidence: 91%
“…The PCR reaction conditions for srn821798 were as follows: denaturation at 95°C for 10 s; 40 cycles consisting of 5 s of denaturation at 95°C; and 20 s of annealing at 50°C. The primers for 16S rRNA, gtfB, gtfC, spaP, srtA, ffh, and relA were synthesizedaccording to previous studies[8,[22][23][24].…”
mentioning
confidence: 99%
“…Our previous study (25) revealed that other sRNAs are differentially expressed within acidic environments. Future investigations aim to determine the sRNAs involved in the acid response exhibited by S. mutans, and to understand the molecular mechanisms and regulation of these molecules.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous study, three libraries of sRNAs were constructed and exposed to acidic conditions (25). A total of 91 sRNAs with ≥1,000 mean reads were identified and nine candidates were randomly selected (Table I).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%